Olives - Therios, Ioannis Nikolaos (Crop production science in horticulture, 2009)
This book of 'olives' is the result of many years' endeavours in collecting valuable information from the existing literature concerning the olive tree and its culture; a proportion of this information, and experience, has originated from scientific projects of the author and his scientific team. Topics include all aspects of olive culture, from its history, through traditional practices to modern techniques and horticultural procedures. Furthermore, this book covers the basic physiological and horticultural principles of olive culture in both theory and practice. The objective is to provide knowledge appropriate for students, scientists, both experienced and inexperienced horticulturists and, in general, for anyone wishing to obtain knowledge and experience of olive culture to increase productivity and improve product quality.